2020
DOI: 10.3233/jnr-190126
|View full text |Cite
|
Sign up to set email alerts
|

Neutron activation properties of PE-B4C-concrete assessed by measurements and simulations

Abstract: The neutron activation properties of the PE-B4C-concrete recently developed for the European Spallation Source (ESS) ERIC (European Spallation Source, https://europeanspallationsource.se/about) were investigated. On the one hand the concrete activation was compared to that of the ordinary concrete from which it was developed by means of irradiating concrete samples in the Budapest Research Reactor (BRR) (Budapest Neutron Centre, https://www.bnc.hu/). On the other hand, the measured activities were used to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The other researchers have examined the activation of concrete in the nuclear reactors [7] and accelerators [8]. However, materials of concrete may differ depending on their sand, cement, and aggregate.…”
Section: Introduction *mentioning
confidence: 99%
“…The other researchers have examined the activation of concrete in the nuclear reactors [7] and accelerators [8]. However, materials of concrete may differ depending on their sand, cement, and aggregate.…”
Section: Introduction *mentioning
confidence: 99%
“…Currently, the majority of research related to the activation of shielding concrete relays on Monte Carlo simulations, [10,11]. Park et al [10] investigated the activation characteristics of concretes containing boron carbide and polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Their computational study revealed that the total activity levels of the concrete decreased considerably with an increase with the replacement levels of polyethylene in borated concrete. Hajdu et al [11] simulated an irradiation scenario of concrete bunker and they have found that decay gamma dose rates of concrete activation were about 50% higher with the use of the each concrete constituent measurement-based input compared to the average overall results. They highlighted the importance of precise estimation of trace elements in materials in relation to safety planning and decommissioning of nuclear related constructions.…”
Section: Introductionmentioning
confidence: 99%